Advances in molecular and cell biology. Volume 16, Cell adhesion - Colman, D. (David); ScienceDirect eBooks (Greenwich, CT : JAI Press, 1996)
One prerequisite for the evolution of multicellular organisms was the invention of mechanisms by which cells could adhere to one another. At some point in our history, dividing cells no longer went their separate protozoic ways in the primordial oceans, but instead found that by maintaining an association, by sticking together but not fusing, numerous evolutionary advantages became possible. The subsequent development of specialized tissues and organs depended on the elaboration of incredibly sophisticated, regulatable cell-to-cell adhesion mechanisms which are known to operate in biological processes as diverse as the growth of the embryo, the immune response, the establishment of connections between nerve cells, and arteriosclerosis, to name just a few. Although we can only guess at the ancestral mechanisms that fostered the first primitive intercellular unions, some one billion years ago, we now recognize contemporary molecular "themes" with presumably ancient origins that mediate cell-cell interactions. The chapters in this book serve as useful, thought-provoking, but not exhaustive, commentaries on contemporary topics within the broad field of cell adhesion. If the reader detects a slight tilt toward those adhesion molecules that function in the nervous system, this is merely a reflection of this editor's interests, biases, and of course, limitations.
Print version record.
Elsevier
Keywords: Cell adhesion; Molecular biology; Cell adhesion; Molecular biology; Electronic books